2020
DOI: 10.3390/coatings10100946
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Oxidation Resistance, Mechanical, and Tribological Properties of N- and C-Doped Ta-Zr-Si-B Hard Protective Coatings Obtained by Reactive D.C. Magnetron Sputtering of TaZrSiB Ceramic Cathode

Abstract: Coatings in the Ta-Zr-Si-B-C-N system were produced by magnetron sputtering of a TaSi2-Ta3B4-(Ta,Zr)B2 ceramic target in the Ar medium and Ar-N2 and Ar-C2H4 gas mixtures. The structure and composition of coatings were studied using scanning electron microscopy, glow discharge optical emission spectroscopy, energy-dispersion spectroscopy, and X-ray diffraction. Mechanical and tribological properties of coatings were determined using nanoindentation and pin-on-disk tests using 100Cr6 and Al2O3 balls. The oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
0
8
0
4
Order By: Relevance
“…Indeed, the wear test of the N10 sample ended at the maximum depth corresponding to the interface between the CL and the DZ. The latter is usually characterized by good wear resistance [3,29]. The duplex-treated N20 sample had a specific wear coefficient that was twice as high as that of the previous one.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, the wear test of the N10 sample ended at the maximum depth corresponding to the interface between the CL and the DZ. The latter is usually characterized by good wear resistance [3,29]. The duplex-treated N20 sample had a specific wear coefficient that was twice as high as that of the previous one.…”
Section: Discussionmentioning
confidence: 95%
“…where K-sputtering yield, j-ion current density to a substrate (A/µm 2 ), M 2 -molar weight of substrate material (g/mol), N A -Avogadro's number (mol −1 ), ρ-density of substrate material (g/µm 3 ), q e -elemental charge (C). Only argon ions were involved in the calculations of sputtering rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous Cr2O3 tribofilms were observed at 400 °C , while at 600 °C , continuous Al2O3 and Cr2O3 with a small fraction of discontinuous B2O3/B(OH)3 tribofilms were obtained, and at 800 °C , a stable and continuous B2O3/B(OH)3 tribofilm was formed as a protective layer of the coating from wear. Korneev et al[98] also observed improved mechanical, HT tribological, and oxidation resistance with C and N doping, when they fabricated TaZrSiBCN hard coatings through a sputtering technique.…”
mentioning
confidence: 97%
“…Moreover, they also provide enhanced corrosion and oxidation resistance properties even at high temperatures [46][47][48]. Chromium (Cr), Titanium (Ti), tungsten (W) based binary and ternary alloy and multilayer thin films have shown enhanced hardness of around ∼25-35 GPa whereas they have also reflected good oxidation resistance properties up to ∼500 °C-600 °C [49,50]. It is reported that the mechanical and tribological properties of these coatings are generally rehabilitated by opting appropriate technique of deposition with optimized process parameters, heat treatment processes, impurities, residual stresses, tip geometry and dislocation density of the film [8].…”
mentioning
confidence: 99%